Analisis Peran Petani Kopi Sukamakmur Dalam Mewujudkan Kontinuitas Pasokan Kopi Yang Berkualitas Untuk Home Coffee Roastery Bogor - Andarini, Safina Sekar; Hadi, Cecilia Sri (Jurnal Ilmiah Pariwisata Kesatuan, 2024)
Indonesia has many rich natural resources, especially plantations and agriculture. This country has great potential and is considered the second largest producer in the world after Brazil. In addition, coffee agrotourism and coffee plantations promote sustainable aspects of tourism. Farmers are the main actors who play a role in increasing crop productivity. With demand for coffee increasing every year, how do farmers maintain continuity of coffee supply? This then became the basis for the birth of research entitled "Analysis of the Role of Sukamakmur Coffee Farmers in Realizing Continuous Supply of Quality Coffee for Home Coffee Roastery Bogor". The aim of this research is to analyze the role of farmers in realizing sustainable coffee production. This research brings qualitative closer. The data collection method was carried out by interviewing informants with direct field observation and documentation. The results of this research are seen from the aspect of farmers from the general community group in Sirnajaya Village, Sukamakmur Regency, who succeeded in producing quality coffee beans to supply at Home Coffee Roastery Bogor, by paying attention to the post-harvest process, special training for farmers, and prioritizing specific quality and quantity.   Keywords : Coffee farmer, Productivity, Coffee Industry.